Tratados Quadragesimais e da Páscoa, de Antônio Feo: edição crítica dos seis últimos tratados da Semana Santa - Celso Reis Macedo (2009)
This dissertation presents a critical edition of the last six Tratados da Semana Santa enclosed in Frei Antonio Feos (1572-1627) Tratados Quadragesimais e da Páscoa da Ordem dos Pregadores. Studies about this piece of work - written in the Portuguese language - are justified by the fact that it is now completing 400 years since its first edition, added to its importance to the studies of Holy Eloquence, literature of conventsin the seventeenth century and studies of the genre treatises. This research is divided into four parts: the introduction justifies the edition of the last six Tratados da Semana Santa; the first chapter brings information about the author (Frei Antonio Feo), as wellas the tradition of the work such as its historical context. As we are dealing with a religious text, a brief study of the adopted doctrine is also available. Based on the bibliography, we present the historical journey, the testimonies which were found and the stemma of the text. The second chapter presents the abbreviations of the collatededitions, the editing norms adopted in the establishment of the critic text, the text itself and the critic apparatus. Finally, the appendices offer the diplomatic edition of the 1612 edition, along with a strictly conservative transcription of all the elements in the model, so as to facilitate the reading; as well as an appendix containing the cover sheets of theconsulted editions.